(untitled) (The Peerian Journal, 2024)
In vitro fertilization (IVF) and intracytoplasmic sperm injection (ICSI) are two important subtypes of assisted reproductive technologies used to treat infertility. Predicting the outcome of IVF/ICSI implantation or the likelihood of pregnancy is essential for infertile couples as these treatments are complex and expensive, and the probability of conception is low.